BNDES Exim e o financiamento às exportações: impactos no emprego das firmas e salário dos empregados - Deus, Guilherme Brito Brandão Ferreira de (2025)
BNDES Exim is an export promotion policy of the Brazilian development bank (BNDES) which aims to boost Brazilian firms’ access to foreign markets. This study presents the first evaluation of the BNDES Exim’s impacts on the employment level of beneficiary firms and on workers’ hourly wages. Accordingly, this work employs two original databases, which were built using three sources: the list of BNDES Exim beneficiaries, the Secretariat of Foreign Commerce (SECEX) list of exporters, and the Annual Report of Social Information (RAIS) from the Brazilian Ministry of Labor and Employment (MTE). This study consists of two autonomous papers in accordance with the variables analyzed. The Brazilian literature on BNDES Exim has found that it increases the export value of its beneficiaries. However, there is a time gap in the literature, since the last study that used microdata was from 2014. Moreover, the literature has not analyzed the employment level and wages yet. This study aims to fill these gaps and expects to further the literature by evaluating if there are any impacts on employment-related variables. These impacts are evaluated according to the learning-by-exporting hypothesis. The results show no evidence of increase in employment level due to a firm receiving funding from the program. Furthermore, the findings suggest that workers from large firms experience a reduction of 8,9% on their wages. However, workers from micro, small and medium-sized firms experience an increase of around 2% on their wages. The findings point to a joint conclusion about the policy: it should be redesigned to focus micro, small and medium-sized firms.